2012
DOI: 10.1007/bf03261999
|View full text |Cite
|
Sign up to set email alerts
|

Individual NSAIDs and Upper Gastrointestinal Complications

Abstract: Background: The risk of upper gastrointestinal (GI) complications associated with the use of NSAIDs is a serious public health concern. The risk varies between individual NSAIDs; however, there is little information on the risk associated with some NSAIDs and on the impact of risk factors. These data are necessary to evaluate the benefit-risk of individual NSAIDs for clinical and health policy decision making. Within the European Community’s Seventh Framework Programme, the Safety Of non-Steroidal anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(151 citation statements)
references
References 71 publications
(151 reference statements)
5
109
1
14
Order By: Relevance
“…Ketoprofen, naproxen and ketorolac tend to exhibit more aggressive gastrointestinal effects than ibuprofen or celecoxib [18-20]. We found that individuals taking ibuprofen or celecoxib had similar gut microbiome profiles, while those taking naproxen or ketorolac had distinctly different profiles.…”
Section: Discussionmentioning
confidence: 77%
“…Ketoprofen, naproxen and ketorolac tend to exhibit more aggressive gastrointestinal effects than ibuprofen or celecoxib [18-20]. We found that individuals taking ibuprofen or celecoxib had similar gut microbiome profiles, while those taking naproxen or ketorolac had distinctly different profiles.…”
Section: Discussionmentioning
confidence: 77%
“…Large pooled data showed that the predicted absolute annual risk of upper gastrointestinal complications was lower for COX-2 inhibitors than naproxen and ibuprofen. 7 However, COX-2 inhibitors are associated with an increased risk of cardiovascular events. There is little evidence of an increased risk of cardiovascular complications with use of a low dose of diclofenac.…”
Section: Resultsmentioning
confidence: 99%
“…Until 2004, however, the dominant discourse on NSAID toxicity concerned gastrointestinal bleeding. Among the traditional NSAIDs, ibuprofen has a well-established low gastrointestinal risk, whereas the gastrointestinal safety is lower for naproxen 31,32. Although the magnitude of cardiovascular versus gastrointestinal risks for individual NSAIDs is controversial,33 it is possible that preferences to a large extent still are driven mainly by the perceived gastrointestinal risks.…”
Section: Discussionmentioning
confidence: 99%